The development of occupational safety and health in Kenya: challenges, priorities and practitioner role - Chacha, Mbusiro (2020)
There have been recent changes in the world of work resulting from the effects of globalisation and industrialisation. Developing countries are striving to catch up with developed countries through the process of modernisation. Kenya is a fast-growing economy that aims to be a highly industrialised country by the year 2030. As a result, workers have been exposed to work-related risks affecting their health and safety. There are new work patterns, technologies, and machineries that have exposed workers to occupational accidents and diseases. The extent to which health and safety practitioners (HSPs) have awareness of and understand current and emerging risks is unclear. There are also concerns that existing occupational safety and health (OSH) legislation does not address all aspects of OSH, such as psychosocial risks. Additionally, there is a lack of clarity regarding the level of expertise of OSH practitioners. This investigation was designed to obtain a deeper understanding of OSH management and practice in Kenya. The aim of the research was to investigate the current status of OSH in Kenya by exploring emerging OSH challenges, identifying practitioner training needs, and future priorities for improving OSH. Further, the research explored the practitioner’s role in supporting OSH.